SEED METERING MECHANISMS AND TRACTOR-SEEDER FORWARD SPEED ON CORN AGRONOMIC COMPONENTS - Cortez,Jorge W. (2020)
ABSTRACT Seed metering system and tractor-seeder forward speed are factors that affect sowing. Therefore, this study aimed to evaluate sowing and agronomic components of corn as a function of seed metering mechanism and tractor-seeder forward speed, in addition to evaluating the yield data obtained from a harvester with a yield monitor. The soil of the area is classified as Distroferric Red Latosol. The experiment was set up in the second crop season of 2018 and treatments consisted of two seed metering mechanisms (M) (pneumatic and mechanical), and tractor-seeder forward speeds (S) (3, 5, 7, and 9 km h−1). The pneumatic system promoted the best longitudinal distribution, with values above 90%, and the increased sowing forward speed reduced normal spacings and increased failure. The interaction M × S indicated that pneumatic seeder promotes the best stand at the highest forward speed, normal spacing, and less failure. The yield data showed less variation with increasing forward speed, and the best result was observed for the mechanical seeder at 5 km h−1 when these data are grouped into yield classes.